Analysis of the genotype × environment interactions and assessment of the adaptability potential in barley under the conditions of the Northern Trans-Urals - N. V. Tetyannikov; N. A. Bome (Труды по прикладной ботанике, генетике и селекции)
Background. Crop yield is a compound and complex character in breeding programs. A stable high yield is determined by the genotype, environmental impacts, and their interaction. A comprehensive assessment of cultivars based on their adaptability, plasticity and stability makes it possible to select among the studied assortment the most promising, potentially high-yielding and environmentally flexible plant forms adaptable to a wide range of environmental conditions.Materials and methods. Evaluation of 146 accessions representing two-row (subsp. distichon L.) and six-row (subsp. vulgare) barleys (Hordeum vulgare L.) was performed in 2015–2017 to measure the adaptability, stability, plasticity and homeostasis of barley yield. Experimental data were statistically processed using the methods of the two-way ANOVA and correlation analysis.Results and conclusion. It was established that barley yield formation was almost equally determined by the genotype (34.3%), environmental conditions (31.9%), and genotype × environment interactions (33,7%), showing that the tested barleys were relatively well adaptable to climate changes in the Northern Trans-Urals. Barley yield was more closely associated with grain weight per plant (r = 0.72) and the number of productive stems per area unit (r = 0.63), and to a lesser extent with seed germination rate in the field (r = 0.39) and 1000 grain weight (r = 0.37). Strong correlations were observed for the yield with the adaptability coefficient (r = 0.94), environmental plasticity index (r = 1.00), and compensatory capacity (r = 0.96). Cvs. ‘Abyssinian 14’ (k-23504, var. pallidum) and ‘Kharkovsky 70’ (k-23683, var. nutans) exhibited a set of adaptive and productive properties.